2020
DOI: 10.1007/s12192-019-01062-3
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of mutations in the genes of the ER export machinery COPII in vertebrates

Abstract: Coat protein complex II (COPII) plays an essential role in the export of cargo molecules such as secretory proteins, membrane proteins, and lipids from the endoplasmic reticulum (ER). In yeast, the COPII machinery is critical for cell viability as most COPII knockout mutants fail to survive.In mice and fish, homozygous knockout mutants of most COPII genes are embryonic lethal, reflecting the essentiality of the COPII machinery in the early stages of vertebrate development.In humans, COPII mutations, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…For example, COPII mediates nutrient availability in the metabolic control of liver protein and lipid trafficking in mammals. 31,32 Homozygous knockout mutants of COPII can induce embryonic lethality in mice and fish, 33,34 and in humans, COPII mutations cause diseases with distinct clinical features. 34 Recent studies demonstrated the diverse roles of COPII in several insects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, COPII mediates nutrient availability in the metabolic control of liver protein and lipid trafficking in mammals. 31,32 Homozygous knockout mutants of COPII can induce embryonic lethality in mice and fish, 33,34 and in humans, COPII mutations cause diseases with distinct clinical features. 34 Recent studies demonstrated the diverse roles of COPII in several insects.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Homozygous knockout mutants of COPII can induce embryonic lethality in mice and fish, 33,34 and in humans, COPII mutations cause diseases with distinct clinical features. 34 Recent studies demonstrated the diverse roles of COPII in several insects. Studies showed that COPII is required for embryonic development in Drosophila melanogaster 35 and vitellogenesis in Aedes aegypti.…”
Section: Introductionmentioning
confidence: 99%
“…7, 8). COPII mutations are reported to cause ER stress, which has been interpreted as resulting from the accumulation of secretory proteins that cannot travel to the Golgi (33), but an additional cause might be an outcome of ERAD inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Sec13/Sec31 heterodimers complete membrane curvature and COPII vesicle formation (Fath et al, 2007;Stagg et al, 2008). Since their discovery in yeast cells, it has become clear through subsequent work that COPII components play important roles in the development of human diseases (Lu and Kim, 2020), so much that the work of their discoverer Randy Shekman has been acknowledged with the 2013 Nobel Prize in Physiology and Medicine. Indeed, mutations in genes encoding Sec23A lead to the accumulation of unsecreted procollagen within the ER and, consequently, to collagen deposition defects followed by skeletal and developmental alterations, as revealed in a rare genetic disease known as craniolenticulo-sutural dysplasia (LSD) (Boyadjiev et al, 2006).…”
Section: The Upr and The Multitasking Control Of Protein Foldingmentioning
confidence: 99%